Proceedings Scalable High Performance Computing Conference SHPCC-92.
DOI: 10.1109/shpcc.1992.232677
|View full text |Cite
|
Sign up to set email alerts
|

Phase modeling of a parallel scientific code

Abstract: This paper describes a performance model f o r a parallel program that solves the nonlinear shallow water equations using the spectral tranform method. The model is generated via a phase analysis, and consists of a sequence of simple models whose sum describes the performance of the entire code. This use of a sequence of simple models increases the range of validity of the model as the problem and machines parameters scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In earlier research, we showed that different logical phases of a code may need to be modeled individually [30]. Each phase has its own computation rate, depending on the amount of computation and the amount and pattern of memory accesses.…”
Section: Modeling Pstswmmentioning
confidence: 99%
“…In earlier research, we showed that different logical phases of a code may need to be modeled individually [30]. Each phase has its own computation rate, depending on the amount of computation and the amount and pattern of memory accesses.…”
Section: Modeling Pstswmmentioning
confidence: 99%